2014
DOI: 10.1177/1056789514529984
|View full text |Cite
|
Sign up to set email alerts
|

Toughness enhancement in architecturally modified Al6061-5 vol.% SiCp laminated composites

Abstract: Damage tolerance improvement in discontinuously reinforced aluminum matrix composites has been examined through both extrinsic and intrinsic approaches by researchers. In this study, extrinsic mechanism was considered in the form of architectural modification in laminates comprising two exterior layers of Al6061-5 vol.% SiCp and an interlayer of Al1050. Hot roll bonding was utilized to fabricate laminates since interfacial adhesion of layers was controlled by means of rolling strain. The interfacial strength a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Of the above, the tribological performance of the composite is of paramount concern for the components, namely, engine piston, cylinder liner, piston rings, and vehicle brakes, etc. 3,4 The above properties of the composite materials depend on the size, shape, loading of the particles, inter-particle spacing, and the particle-matrix interface. Besides, the thermodynamic stability of reinforcement, interfacial bonding strength at high temperature, has also got great importance in the selection of AMC for the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…Of the above, the tribological performance of the composite is of paramount concern for the components, namely, engine piston, cylinder liner, piston rings, and vehicle brakes, etc. 3,4 The above properties of the composite materials depend on the size, shape, loading of the particles, inter-particle spacing, and the particle-matrix interface. Besides, the thermodynamic stability of reinforcement, interfacial bonding strength at high temperature, has also got great importance in the selection of AMC for the automotive industry.…”
Section: Introductionmentioning
confidence: 99%
“…Jing et al [17] has also indicated the same kind of effect of rolling thickness reduction on bond quality. Monazzah et al [18] found that micro-cracks available on surfaces to be bonded together facilitate the bonding process. The study further revealed that fracture toughness, bond strength and rolling thickness reduction have a direct relation.…”
Section: Results and Discussion For Experimental Interface Characterimentioning
confidence: 99%
“…Monazzah et al [24] indicated that intrinsic toughening had influence on the fracture resistance of composite materials based on inherent resistance of its microstructure to crack nucleation. The microstructure includes the morphology and size of reinforced phase particle.…”
Section: Introductionmentioning
confidence: 99%